Fostering digital transformation of SMEs: a four levels approach. Issue 8 (17th March 2020) - Garzoni, Antonello; De Turi, Ivano; Secundo, Giustina; Del Vecchio, Pasquale
Abstract : Purpose: The purpose of this paper is to analyse how digital technologies trigger changes in the business process of manufacturing small and medium-sized enterprises (SMEs) in the Apulia Region (South Italy). As SMEs play an essential role in the process value creation of industries and countries, the article examines the enablers of Industry 4.0 in a regional contexts characterized by delay in research and development and innovation performances where the companies' competitiveness is based on limited knowledge and technological assets. Design/methodology/approach: The case study of Smart District 4.0, an ongoing project aimed to promote the digitalization of SMEs operating in the Agri–Food, Clothing–Footwear and Mechanics–Mechatronics in the Apulia Region (South Italy) is analysed. The project has been financed by the Italian Ministry of Economic Development with the final aim to sustain the digital transformation of SMEs in South Italy. Findings: The results introduce a four levels approach of engagement of SMEs in the adoption of digital technologies, namely, digital awareness, digital enquirement, digital collaboration and digital transformation. Furthermore, for each level of engagement the study describes and discusses some relevant variables that could be used by managers and entrepreneurs to assess the level of readiness for utilization of digital technologies and how to digitalize some processes. Practical implications: Practical implications regard the definition of a roadmap useful to assess and manage the level of digital transformation of SMEs. Limitations of the study regarding the temporal dimension of the evidences associated to the Smart District 4.0 as well as to the regional context was analysed. Originality/value: Originality resides in the definition of a roadmap for the digital transformation of SMEs in a region where the profile of companies' digital maturity is still low.